A Multi-Systems Approach to Human Movement after ACL Reconstruction: The Integumentary System - Kathryn Lucas; Patricia Todd; Brandon M Ness (North American Sports Medicine Institute, 2021)
Postoperative management of anterior cruciate ligament (ACL) reconstruction has traditionally focused on the evaluation and intervention of musculoskeletal components such as range of motion and patients' reports of function. The integumentary system can provide early indications that rehabilitation may be prolonged due to protracted or poor healing of the incision sites. Full evaluation of the reconstruction over time, including direction of the incisions, appearance of surgical sites, level of residual innervation, and health of the individual should be considered when determining time-based goals and plans for returning an athlete to activity. Skin care techniques should be used to minimize strain and promote wound healing at the surgical sites, which in turn allows for implementation of other interventions that target other body systems such as locomotion, strength training, and cardiopulmonary conditioning. The integration of the integumentary system with cardiovascular, neurological, and muscular systems is required for a successful return to activity. A multi-physiologic systems approach may provide a unique viewpoint when aiming to attain a greater appreciation of the integumentary system and its integration with other body systems following ACL reconstruction. The purpose of this clinical commentary is to discuss integumentary considerations within a multi-physiologic systems approach to human movement after ACL reconstruction, including an anatomical review, key elements of assessment, and integrated intervention strategies. # Level of Evidence 5